Grade of Disability and Perceived Stigma of Leprosy Patients : is there any relationship? Relationship of Grade of Disability and Perceived Stigma of Leprosy Patients - Dalimunthe, Dina Arwina; Sinambela, Duma Wenty Irene; Lubis, Syahril Rahmat (Journal of Pakistan Association of Dermatologists, 2023)
Abstract Background: Leprosy can remain with residual disabilities and advance slowly. One of the main causes of stigma was the visible disabilities caused by leprosy. Stigma and disability are still problems for handling leprosy. Correlation of disability and stigma in leprosy is well known, but the correlation between the grading of disability towards stigma is still debatable and lack of study. This study aims to determine the relationship between the grade of disability according to WHO (World Health Organization) and the perceived stigma of leprosy patients. Methods: Cross-sectional research methods with consecutive sampling were employed by the researchers to analyze 30 leprosy patients in this observational study. On research participants, parameters such as age, gender, type of leprosy, and disability grade using the WHO classification system were assessed. The Explanatory Model Interview Catalogue (EMIC) score was used to evaluate perceived stigma. The One-Way Anova test is used to examine the relationship between the WHO disability grade and perceived stigma in leprosy patients. Results: The result of this study is that there is no significant relationship between the grade of leprosy disability and perceived stigma, p=0.752. The majority of these studies participants are between the ages of 19 and 40, male, multibacillary leprosy, grade 0 leprosy disability, and have a negative perceived stigma. Conclusion: There is no significant relationship between the grade of leprosy disability and perceived stigma. Keywords: Explanatory Model Interview Catalogue; Grade of disability; Leprosy; Perceived stigma.